2023
DOI: 10.1007/s10787-023-01162-8
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular compatibility of an injectable anti-inflammatory nanodispersion from a standardized Bixa orellana oil (Chronic®): a toxicological study in Wistar rats

Abstract: Bixa orellana L. is a plant popularly known as "ucurum", "annatto", and "achiote". It is native to South America, and its seeds are an abundant source of geranylgeraniol and tocotrienols. Nanoencapsulation is a valuable technique that can decrease the drug needed to achieve an effect, decreasing potential toxicity and side effects. This study aimed to evaluate the acute toxicity of an intramuscular application of a nanodispersion containing a standardized extract (Chronic®) from the seeds of Bixa orellana (NBO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…The oil derived from B. orellana, which is included in the formulation of Terasen ® , contains δtocotrienol and geranylgeraniol as its main compounds. Previous studies have reported the presence of δ-tocotrienol in the seeds of B. orellana [35][36][37] and geranylgeraniol [37,38].…”
Section: Discussionmentioning
confidence: 97%
“…The oil derived from B. orellana, which is included in the formulation of Terasen ® , contains δtocotrienol and geranylgeraniol as its main compounds. Previous studies have reported the presence of δ-tocotrienol in the seeds of B. orellana [35][36][37] and geranylgeraniol [37,38].…”
Section: Discussionmentioning
confidence: 97%